ANALISIS KOMPETENSI PROFESIONAL GURU PAUD DALAM MERANCANG PEMBELAJARAN TEMATIK YANG BERMAKNA BAGI ANAK USIA DINI - Assyifa Mulya, Ghani; Amanda, Rezky Tri; Amelia, Nabila; Alifah, Ayu; Kurnia, Rita (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study aims to evaluate the professional competence of Early Childhood Education (ECE) teachers in designing meaningful thematic learning for young children at TK Al Rasyid. The background of this research arises from the phenomenon that thematic learning, which should be child-centered, often remains administrative in nature and lacks the reflective qualities expected of professional educators. The main problem lies in teachers’ limited ability to connect lesson planning with developmental assessments of children and the absence of reflective practices in their teaching process. This study employed a qualitative descriptive method with data collected through observation, interviews, and documentation. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results reveal that ECE teachers at TK Al Rasyid have demonstrated a basic understanding of the concept of thematic learning; however, its implementation remains focused on administrative tasks rather than reflective and developmental aspects. Lesson plans are not yet fully based on children’s actual needs and interests, and learning activities tend to be teacher-centered, limiting children’s exploration. Moreover, reflective practices after learning have not become a consistent part of teachers’ professional routines. These findings indicate that the professional competence of ECE teachers at TK Al Rasyid is still at an early stage of development. Therefore, strengthening programs through reflective training, continuous supervision, and the cultivation of evaluative habits are essential to help teachers design more meaningful, contextual, and child-centered thematic learning experiences.